MULTILINGUALISM AND MULTICULTURALISM IN EDUCATIONAL UZBEK CONTEXTS - Sanakulov Jahongir Xudayberdiyevich (Western European Studies, 2024)
This article explores the impact of multilingualism and multiculturalism on education in Uzbekistan. It examines how historical, cultural, and social dynamics have shaped educational policies and practices. The study highlights the integration of Uzbek, Russian, and English in the curriculum, reflecting both national identity and global communication needs. The findings reveal a complex interplay between maintaining linguistic heritage and embracing global linguistic trends, underscoring the importance of fostering intercultural competence in a diverse educational landscape
Keywords: Multilingualism; Multiculturalism; Education